Unveiling signaling pathways inducing MHC class II expression in neutrophils - Forrer, Pascal; Palianina, Darya; Stühler, Claudia; Kreuzaler, Matthias; Roux, Julien; Li, Jiagui; Schmutz, Christoph; Burckhardt, David; Franzeck, Fabian; Finke, Daniela; Schmidt, Alexander; Bumann, Dirk; et al. (Frontiers in Immunology, 2024)
Introduction Gram-negative bacillary bacteremia poses a significant threat, ranking among the most severe infectious diseases capable of triggering life-threatening sepsis. Despite the unambiguous involvement of neutrophils in this potentially fatal disease, there are limited data about the molecular signaling mechanisms, phenotype, and function of human neutrophils during the early phase of gram-negative bacillary bacteremia. Methods By using an unbiased proteomics and flow cytometry approach, we identified an antigen-presenting cell (APC)-like phenotype in human peripheral blood neutrophils (PMN) with MHC class II molecule expression in the early phase of bacteremia. Using an in-vitro model of GM-CSF-mediated induction of APC-like phenotype in PMN, we investigated downstream signaling pathways leading to MHC class II expression. Results GM-CSF stimulation of neutrophils leads to the activation of three major signaling pathways, the JAK-STAT, the mitogen-activated protein kinase (MAPK), and the phosphoinositide 3-kinase (PI3K)-Akt-mTOR pathways, while MHC class II induction is mediated by a MAPK-p38-MSK1-CREB1 signaling cascade and the MHC class II transactivator CIITA in a strictly JAK1/2 kinase-dependent manner. Discussion This study provides new insights into the signaling pathways that induce MHC class II expression in neutrophils, highlighting the potential for therapeutic targeting of JAK1/2 signaling in the treatment of gram-negative bacteremia and sepsis. Understanding these mechanisms may open up novel approaches for managing inflammatory responses during sepsis.